Liquefaction Of Silts: The Adapazari Criteria - Bol, Ertan; Sert, Sedat; Özocak, Aşkın; AREL, ERSİN; ÖNALP, AKIN (Springer, Van Godewijckstraat 30, 3311 Gz Dordrecht, Netherlands, 2010)
Ground failures in the form of liquefaction, loss of bearing capacity and soil softening have been observed during the 1999 Marmara (Turkey) earthquake. Research to understand the failure phenomena has been carried out since the earthquakes. This paper attempts to provide explanations to the liquefaction failure of silts in seismic conditions. Findings from a large amount of data collected in the city of Adapazari on the physical and mechanical properties of soils is presented. A geomorphological map of the city has shown that there are surprising horizontal and vertical variations of the facies due to the activity of rivers in the past. Cases of liquefaction appear to have concentrated in former backswamp areas where silts and sandy silts were deposited by crevasse splays. Properties of the soils in zones of liquefaction and non-liquefaction have been determined down to a reasonable depth by measuring the average size, clay content and liquidity index as well as cone penetration resistances with porewater pressures to discover that there is significant discrepancy among those profiles susceptible to liquefaction and non-liquefying deposits. A set of "Adapazari Criteria" is proposed which is intended to improve over the "Chinese Criteria" and is simple enough to be universally applicable. This classification is similar to the existing criteria but emphasizes more on the clay content in addition to measuring the liquid limit and the liquidity index as well as the average size.
Keywords: Turkey; Adapazari; Earthquake; Ground failure; Liquefaction; Fine-grained soils; Clay content; Liquidity index; Average size; Sand content; Türkiye; Adapazarı; Deprem; zemin hatası; Sıvılaşma; İnce taneli topraklar; kil içeriği; likidite indeksi; Ortalama boyut; kum içeriği